Foreign Exchange Market Stress in Syria Analytical Study for the Period (2011-2022) (Journal of Hama University, 2025)
This study aimed to evaluate the level of financial stress experienced by the foreign exchange market in Syria as a result of the repercussions of the Syrian crisis that began in 2011. To achieve the goal of the study, quarterly data of the parallel exchange rate of the Syrian pound against the US dollar was used during the period (2011-2022).The descriptive approach was used, and the rate of exchange rate change, realized volatility, and maximum accumulated loss were relied upon as indicators of foreign exchange market stress.The study reached a set of results:- The Syrian crisis and its resulting repercussions greatly affected the exchange rate of the Syrian pound, as the Syrian pound fell 117-fold by the end of 2022. The inconsistent policies of the Central Bank of Syria also played a major role in exchange rate fluctuations and high currency speculation, which led to inflation and large losses in foreign reserves.- According to the CMAXt index, signs of stress in the foreign exchange market began starting in the third quarter of 2012, and during the study period two collapses in exchange rates occurred. The first collapse occurred in the third quarter of 2013, while the second collapse occurred in the first quarter of 2020. It is noticeable that in both cases of collapse there was no recovery or rebound period, but rather stress in the exchange market continued until the fourth quarter of 2022.- Starting from the fourth quarter of 2011, exchange rate fluctuations began and continued until the fourth quarter of 2022. The exchange rate was not characterized by stability, but rather witnessed an increase in the intensity of fluctuations. There were periods of increasing fluctuations and others of decreasing fluctuations, which indicates that the exchange market suffered from financial stress and instability according to the realized volatility index.
Keywords: Foreign exchange market stress; rate of change of exchange rate; realized volatility; maximum accumulated loss